Genetic Modification of Closely Related Candida Species - Mancera, Eugenio; Frazer, Corey; Porman, Allison M.; Ruiz-Castro, Susana; Johnson, Alexander D.; Bennett, Richard J. (Frontiers in Microbiology, 2019)
Species from the genus Candida are among the most important human fungal pathogens. Several of them are frequent commensals of the human microbiota, but are also able to cause a variety of opportunistic infections, especially when the human host becomes immunocompromised. By far, most of the research to understand the molecular underpinnings of the pathogenesis of these species has focused on Candida albicans, the most virulent member of the genus. However, epidemiological data indicates that related Candida species are also clinically important. Here, we describe the generation of a set of strains and plasmids to genetically modify Candida dubliniensis and Candida tropicalis, the two pathogenic species most closely related to C. albicans. C. dubliniensis is an ideal model to understand C. albicans pathogenesis since it is the closest species to C. albicans but considerably less virulent. On the other hand, C. tropicalis is ranked among the four most common causes of infections by Candida species. Given that C. dubliniensis and C. tropicalis are obligate diploids with no known conventional sexual cycle, we generated strains that are auxotrophic for at least two amino acids which allows the tandem deletion of both alleles of a gene by complementing the two auxotrophies. The strains were generated in two different genetic backgrounds for each species — one for which the genomic sequence is available and a second clinically important one. In addition, we have adapted plasmids developed to delete genes and epitope tag proteins in C. albicans so that they can be employed in C. tropicalis. The tools generated here allow for efficient genetic modification of C. dubliniensis and C. tropicalis, and thus facilitate the study of the molecular basis of pathogenesis in these medically relevant fungi.